Irish Media Coverage of COVID-19 Evidence-Based Research Reports From One National Agency - Melissa K. Sharp; Zoë Forde; Cordelia McGeown; Eamon O’Murchu; Susan M. Smith; Michelle O’Neill; Máirín Ryan; Barbara Clyne (International Journal of Health Policy and Management, 2022)
Background  How research findings are presented through domestic news can influence behaviour and risk perceptions, particularly during emergencies such as the coronavirus disease 2019 (COVID-19) pandemic. Monitoring media communications to track misinformation and find information gaps is an important component of emergency risk communication. Therefore, this study investigated the traditional media coverage of nine selected COVID-19 evidencebased research reports and associated press releases (PRs) published during the initial phases of the pandemic (April to July 2020) by one national agency.Methods  NVivo was used for summative content analysis. ‘Key messages’ from each research report were proposed and 488 broadcast, print, and online media sources were coded at the phrase level. Manifest content was coded and counted to locate patterns in the data (what and how many) while latent content was analysed to further investigate these patterns (why and how). This included the coding of the presence of political and public health actors in coverage.Results  Coverage largely did not misrepresent the results of the reports, however, selective reporting and the variability in the use of quotes from governmental and public health stakeholders changed and contextualised results in different manners than perhaps originally intended in the PR. Reports received varying levels of media attention. Coverage focused on more ‘human-interest’ stories (eg, spread of COVID-19 by children and excess mortality) as opposed to more technical reports (eg, focusing on viral load, antibodies, testing, etc).Conclusion  Our findings provide a case-study of European media coverage of evidence reports produced by a national agency. Results highlighted several strengths and weaknesses of current communication efforts.